ANALYSIS OF THE EFFECT OF CAR, BOPO, NPL, LDR, AND SIZE ON PROFITABILITY OF BANKS LISTED ON IDX PERIOD 2016-2020 - ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
Banking is a bank that has a role in the financial system in Indonesia. The existence of the banking sector has an important role, in which most people's lives involve services from the banking sector. Therefore banks in this case must maintain and improve the health of a bank. In doing their operations, one of them is the bank's goal is to get a high return that can be used to fund the development of the operation until with steady expansion in the future. The ability of the bank to earn profit can be assessed by using the ratio of profitability. One of them is Return On Assets (ROA). This study aims to analyze the influence of Capital Adequacy Ratio (CAR), Operational Efficiency (BOPO), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) on Return On Assets (ROA) of banking companies listed in Indonesia Stock Exchange (IDX). Sampling in this study used purposive sampling method. The sample used is 36 companies from 46 companies listed on the IDX that publish annual reports complete from 2016-2020. The data were analyzed using multiple linear regression. Based on the results of the study found that the internal factors of the bankCapital Adequacy Ratio (CAR)andNon Performing Loan (NPL)have a significant effect on the profitability (ROA) of banking companies listed in Indonesia Stock Exchange (IDX) 2016-2020, while the Operational Efficiency (BOPO), Loan to Deposit Ratio (LDR) and Company Size (SIZE) do not have a significant effect on the profitability (ROA) of banking companies listed in Indonesia Stock Exchange (IDX) 2016-2020.